Trace and rare-earth elements in garnets from silicate-carbonate formations of the Kusa-Kopan complex (Southern Urals) - Stativko, V. S.; Skublov, S. G.; Smolenskiy, V. V.; Kuznetsov, A. B. (Litosfera (Ekaterinburg. Online), 2023)
Research subject. Garnets from silicate-carbonate formations and their halos with skarn mineral associations, developedin the historical mines and pits of the Southern Urals: Zelentsovskaya, Nikolaje-Maximilianovskaya, Akhmatovskaya,Perovskitovaya, Gubensky massif, Praskovie-Evgenyevskaya and Shishimskaya. Aim. To study the nature of silicate-carbonate formations of debatable origin. Materials and methods. The composition of garnets distributed both in silicate-carbonate formations and in rocks with skarn mineral associations was analyzed using SEM-EDS (IPGG RAS) and SIMS (Yaroslavl branch of IPT RAS). Results. The garnets from silicate-carbonate rocks show predominantly a dark to black color, a combination of simple rhombododecahedron and tetragontrioctahedron shapes. In terms of composition, these materials correspond to andradite – Ti-andradite, with the share of shorlmite and morimotoite end-members reaching 30 %. The garnets from calcareous skarns are reddish in color and have a rhombododecahedric habitus. In terms of composition, these garnets correspond to an andradite-grossular isomorphic series, with the share of shorlomite and morimotite end-members not exceeding 3 %. For these garnets, the content of trace and rare-earth elements was determined for the first time, and a posi tive correlation of Ti with U, Y, Zr, Hf and Nb was established. Figurative points on binary diagrams (in coordinate axes of rare-earth content) are plotted as a trend of garnet composition in the grossular–andradite–Ti-andradite series. Garnets from silicate-carbonate rocks, unlike those from skarn mineral associations, are characterized by an increased rare-earth elements content. The main feature of the rare-earth elements distribution spectra in garnets is a positive Eu-anomaly, which is observed in all studied garnets. Conclusion. The data obtained allowed the authors to assume that garnets from silicate-carbonate formations and their halos were formed as a result of a single geological process, essentially close to skarn formation. The results of the petrographic-mineralogical and geochemical studies assume that the “carbonatite” nature of the silicate-carbo nate rocks of the Southern Urals is unlikely.